Effect of Edible Coating from Avocado Seed Starch with Cinnamon Extract on the Quality of Strawberry Fruit - Novalia Khairunnisa; Sahib Nukatab (CV. HEI PUBLISHING INDONESIA, 2025)
Strawberries are a high-value fruit with significant nutritional benefits but are highly susceptible to postharvest deterioration caused by mechanical, physical, and microbiological factors. To maintain fruit quality, appropriate postharvest treatments such as edible coatings are required. This study aimed to evaluate the effect of avocado seed starch–based edible coatings enriched with cinnamon extract and to determine the optimal concentration for maintaining strawberry quality. A one-factor Completely Randomized Design (CRD) was applied using cinnamon extract concentrations of 0%, 0.5%, and 1% (v/v). The results showed that the edible coating containing 0.5% cinnamon extract was the most effective treatment, maintaining strawberry quality for five days of storage. This treatment resulted in a weight loss of 9.58%, moisture content of 88.67%, firmness of 6.05 N/cm², total soluble solids of 6.85 °Brix, lightness (L*) value of 7.42, and a total microbial count of 2.4 × 10¹ CFU/g.